Statistical analysis supports the size control mechanism of Chlamydia development. - Jinsu Kim; Christine Sütterlin; Ming Tan; German Enciso (PLoS Computational Biology)
Chlamydia is an intracellular bacterium that reproduces via an unusual developmental cycle that only occurs within a eukaryotic host cell. A replicating form of the bacterium (RB) repeatedly divides to produce about a thousand progeny, which convert in a delayed and asynchronous manner into the infectious form (EB). The regulatory mechanisms that control this developmental switch are unknown, but they could potentially include extrinsic signals from the host cell or other chlamydiae, or an intrinsic signal such as chlamydial cell size. In this paper, we investigated the regulation of RB-to-EB conversion by developing and analyzing three mathematical models, each based on a different regulatory mechanism. To test these models, we derived statistical evidence from parameters, including number, size and location of RBs and EBs, obtained from experimental measurements and model fitting. All three models successfully reproduced the experimentally measured timing of RB-to-EB conversion and growth curves of the developmental forms in an infected cell. However, only the size control model, which postulates that RB size is an intrinsic signal that regulates the timing of RB-to-EB conversion, reproduced two additional statistical properties of the intracellular infection. These properties are a positive correlation between the number of RBs and EBs throughout the developmental cycle and the monotonic evolution of the coefficient of variation of EB number. This analysis thus provides support for the size control model.